Localised and limited impact of a dredging operation on coral cover in the northwestern lagoon of New Caledonia. Issue 1 (15th April 2016) - Adjeroud, Mehdi; Gilbert, Antoine; Facon, Mathilde; Foglia, Marion; Moreton, Benjamin; Heintz, Tom
Abstract: We report here an interannual survey (2006–2012) of coral cover in the northwestern lagoon of New Caledonia, to assess the impact of an important dredging operation (August 2008–February 2010) associated with the construction of the largest nickel mining site in the Pacific. A BACI (Before-After Control-Impact) analysis failed to detect any significant interaction between period (before, during, and after dredging) and the category of the stations (impact vs. control). Among the 31 stations surveyed, only seven showed decreasing coral cover during the study period, mainly due to a decline in Acroporidae. However, the relationship between the dredging and this decrease was highly plausible only for one station, situated 0.9 km from the dredging site. High hydrodynamism in the study area, the abundance of resistant corals and efficient protective measures during the dredging operation might explain these localised and limited impacts. Highlights: Dredging operation associated with the largest nickel mining site in the Pacific. Dredging had a localised and limited impact on coral cover. Ecological and physical conditions in the study area may explain these outcomes. Other stressors can be expected following the start of the nickel exploitation.